Study on the reaction of methane hydrate with gaseous CO2 by Raman imaging microscopy. (31st August 2020) - Huang, Xin; Cai, Wenjiu; Zhan, Linsen; Lu, Hailong
Graphical abstract: Highlights: The reaction mechanism of CO2 with CH4 hydrate is studied by Raman imaging. It is feasible for gaseous CO2 to replace CH4 from gas hydrate. The reaction contains two steps: partial decomposition and inefficient replacement. Abstract: In this study, the feasibility of reacting with methane hydrate and sequestering carbon dioxide with gaseous CO2 is examined. In situ observation by Raman imaging microscope provides an in-depth insight into the mechanism of reacting CO2 gas with methane hydrate, leading to the conclusion that the reaction can be divided into two processes. The first is the partial decomposition of methane hydrate after contacting with CO2 gas, causing the generation of micropores inside hydrate. In the second process, CH4 in the large cage of hydrate is replaced slowly by gaseous CO2 and forms a binary mixture hydrate layer. The formation of a CH4 -CO2 mixed hydrate layer provides a shielding effect and prevents CO2 gas from contacting with deeper internal methane hydrates, resulting in a low replacement efficiency.